Virtue Ethics and Organizational Culture Management in Humanitarian Assistance - Płachciak, Adam (Etyka cnoty a zarządzanie kulturą organizacyjną w pomocy humanitarnej, 2024)
Aim: The aim of the article is to investigate the validity of virtue ethics to humanitarian organizational culture management. Methodology: The method applied is basically focused on the analyses of the relevant literature. Results: The results of the paper show that a humanitarian virtuous agency conducted by innate moral qualities can employ standards that are far beyond formal code duties or effectiveness. Implications and recommendations: Virtue ethics, by stressing the importance of motivational aspects, has unquestionable implications in analyses around humanitarian organizational culture management. Originality/value: Motivational aspects become fundamental for relief workers, especially in situations where normality means lack of normality.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2024; vol. 68, nr 3, s. 131-139
Keywords: virtue ethics; humanitarianism; management; values; moral excellence; etyka cnoty; humanitaryzm; zarządzanie; wartości; moralna doskonałość